Effect of Leaves and Fruits Ethanolic Extract of Duranta repens on Mosquito Culex pipens pipens - Baghdad Science Journal (مجلة بغداد للعلوم)
The study aimes to investigate the effects of leaves & fruits ethanolic extract of Duranta repens L. on biological performance for all stages of life cycle of the mosquito Culex pipiens piepiens L., For this purpose the mosquitoes were reared in the laboratory till the fourth generation .Different concentrations of leaves (800,1000,1200,1400ppm) and fruits (800,1000,1200ppm) were tested on (eggs,larval stages,pupal stages and the adult stages). The results revealed that the extracts gave highest mortality rate for the eggs at(100%) compared with control,fruits extract shown highest mortality rate of the four larval instars (100%)at 1200ppm compared with leave extract at(80,50,33.33,20%).Also the extract caused a high mortality rate for pupal stage compared with fruits extract at(76.66,53.33%)respectively.Also ethanolic extract caused a 83.33,76.66% for male &femail. Developmental deformation was observed.. In conclusion, the findings of the present study indicate that the leaves &fruits extracts of Duranta repens L., , can be widely and effectively used in the control of mosquito.